Developing and developed ASEAN-10 economies: converge or diverge? - Habibullah, Muzafar Shah; Chong, Choy Yoke; Din, Badariah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The governments of the ten ASEAN economies recognised substantial disparity in income level among the more developed and the less developed ASEAN economies. We seek to examine whether there is any tendency for such income disparity among ASEAN countries to narrow over the years. In order to fill the existing gap in literature, the present paper aims to examine income convergence and/or divergence in ASEAN incorporated for the possible nonlinearity in economic growth among countries. The KSS-CHLL nonlinear unit root test proposed by Chong et al. (CHLL, 2008) being an extension of the work by Kapetanios et al. (KSS, 2003), allow us to examine nonlinear long-run convergence and nonlinear catching-up hypotheses. This test is applied on the ASEAN-10 countries with respect to ASEAN average covering the period from 1970 to 2015. Nonlinear convergence was detected in Indonesia, Malaysia, Singapore and Thailand during the period from 1980 to 2015, depending on whether a linear or nonlinear trend was included in the test. Similarly, nonlinear convergence was observed in Indonesia, Singapore, and Thailand during the period from 1985 to 2015. However, only Thailand was found to show nonlinear convergence in the period from 1990 to 2015. Overall, Laos exhibited nonlinear catching-up throughout the sub-periods except for the period from 1990 to 2015. Similarly, Cambodia and Vietnam also showed nonlinear catching-up in some of the sub-periods. On the other hand, Brunei, the Philippines and Myanmar had shown divergence consistently in all sub-periods. These results imply that the government of the ASEAN economies have to work harder in order to achieve the aspiration of the ASEAN Economic Community in the long-term future.